Kinetics and inhibition of reverse transcriptase from human and simian immunodeficiency viruses. - Wu, J C (1988)
Reverse transcriptase from the simian immunodeficiency virus (SIV) was found to have kinetic behavior similar to that of enzyme from the human immunodeficiency virus (HIV). Michaelis constants for the substrates TTP and dGTP and inhibition constants for the inhibitors 3'-azido-3'-deoxythymidine 5'-triphosphate, 2',3'-dideoxythymidine 5'-triphosphate, and 2'-3'-dideoxyguanosine 5'-triphosphate were obtained for SIV reverse transcriptase and were found to be similar to the corresponding values for HIV reverse transcriptase. Thus, the interaction of SIV reverse transcriptase with nucleotide analogs appears to be indistinguishable from that of the HIV enzyme, suggesting that SIV/simian acquired immunodeficiency syndrome (SAIDS) is a potentially good model of AIDS.